2019
DOI: 10.1007/978-3-030-13531-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Installation of a Small Building-Mounted Wind Turbine: A Case Study from Idea to Implementation

Abstract: In Belgium, the installation of a small wind turbine on rooftops is still very uncommon. Currently, there is no dedicated legal framework governing the installation on a building. Nevertheless, over the past years, our research group has received several demands from building owners wanting to install one or several turbines on their rooftop. The lack of a dedicated framework requires increased attention throughout the whole procedure. To prevent potentially harmful installations, we developed an approach to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Wind energy has evolved exponentially in the last few years, and its environmental, social, and economic aspects have become more apparent. Noise, vibration, light reflection, visual impacts, effects on birds, and shadows are the most critical environmental issues [168]. Nevertheless, the economic aspects are more complex than the environmental, because economic issues are multidimensional and vary between countries and regions.…”
Section: Environmental Social and Economic Aspectsmentioning
confidence: 99%
“…Wind energy has evolved exponentially in the last few years, and its environmental, social, and economic aspects have become more apparent. Noise, vibration, light reflection, visual impacts, effects on birds, and shadows are the most critical environmental issues [168]. Nevertheless, the economic aspects are more complex than the environmental, because economic issues are multidimensional and vary between countries and regions.…”
Section: Environmental Social and Economic Aspectsmentioning
confidence: 99%
“…vibrations, noise and shadow flicker. Recent papers [18, 38] studied the feasibility of installing SWT (up to 5.2 kW) on high‐rise buildings. They concluded that the installation generally has little impact on the building and its nearby environment.…”
Section: Case Study: Brussels and Its Rooftopsmentioning
confidence: 99%
“…They concluded that the installation generally has little impact on the building and its nearby environment. It should be emphasised that the results of [18, 38] are for particular buildings, and it is not clear to what extent the conclusions can be generalised to other buildings.…”
Section: Case Study: Brussels and Its Rooftopsmentioning
confidence: 99%
“…For these rooftops, photovoltaic (PV) panels are frequently used. In parallel, several building owners have already opted for small building-mounted wind turbines (between 500 W to 5 kW) [1][2][3]. There is little novelty in using rooftops to generate electricity, yet rooftop-mounted hybrid PV/wind systems have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%